2023
DOI: 10.3390/healthcare11091277
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Psychological Resilience: Examining the Impact of Managerial Support on Mental Health Outcomes for Saudi Ambulance Personnel

Abstract: Ambulance personnel are among the groups with high mental health risks. This study aims to investigate the role of managerial support in determining the mental well-being of ambulance personnel, a group at high risk for mental health issues. A descriptive, cross-sectional survey design was conducted in Riyadh, Saudi Arabia, in February 2022, involving a convenience sample of 354 ambulance personnel. An online survey was distributed via social media platforms. Manager behavior and mental well-being were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For instance, it has been found that ambulance personnel with more years of experience demonstrated significant differences in decision-making mechanisms [ 34 ]. Similarly, staff in different professional roles such as doctors, paramedics, and EMTs were found to have varying awareness levels about refusal of treatment as a fundamental patient right [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been found that ambulance personnel with more years of experience demonstrated significant differences in decision-making mechanisms [ 34 ]. Similarly, staff in different professional roles such as doctors, paramedics, and EMTs were found to have varying awareness levels about refusal of treatment as a fundamental patient right [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…With 38.3% underscoring the need for psychological support and counseling access, it is evident that the crisis has had profound mental health implications. Previous studies during past health crises have similarly emphasized the psychological vulnerabilities of frontline healthcare workers, necessitating robust mental health support structures [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based disaster risk reduction (CBDRR) initiatives also form a key part of Saudi Arabia's efforts to enhance public awareness and education. CBDRR initiatives aim to empower communities to understand, assess, and mitigate the risks they face, thereby enhancing their resilience to disasters [17,38,42,43]. For instance, in Jeddah, a community-based initiative was launched to address the recurrent flooding issue in the city.…”
Section: Enhancing Public Awareness and Educationmentioning
confidence: 99%